2006
DOI: 10.1242/jeb.02598
|View full text |Cite
|
Sign up to set email alerts
|

DNA photorepair in echinoid embryos: effects of temperature on repair rate in Antarctic and non-Antarctic species

Abstract: Over recent geological time the Antarctic marine system has been a relatively low ultraviolet radiation (UV-R) environment because of its polar location, high atmospheric ozone concentrations, and extensive seasonal covering by relatively opaque, and highly reflective, sea ice. Recent increases in ultraviolet-B radiation (280-315·nm) due to stratospheric ozone depletion have highlighted the susceptibility of marine ecosystems to this important abiotic factor (Smith et al., 1992;Karentz, 1994;Smith and Cullen, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 45 publications
5
54
0
Order By: Relevance
“…In contrast to temperate and tropical species, the Antarctic embryos accumulated a higher number of CPDs during early development, and were also found to have the highest rates of abnormal embryo development when exposed to both UV-B and UV-A. Lamare et al (2006) showed that DNA repair is slower and likely due to the lack of temperature compensation in the enzyme mediated photorepair process in S. neumayeri. The greater DNA damage in Antarctica may in essence be the result of cold sea temperatures, which while not effecting initial CPD formation (the rate of which should be relatively temperature independent), substantially slows metabolic processes such as DNA repair.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In contrast to temperate and tropical species, the Antarctic embryos accumulated a higher number of CPDs during early development, and were also found to have the highest rates of abnormal embryo development when exposed to both UV-B and UV-A. Lamare et al (2006) showed that DNA repair is slower and likely due to the lack of temperature compensation in the enzyme mediated photorepair process in S. neumayeri. The greater DNA damage in Antarctica may in essence be the result of cold sea temperatures, which while not effecting initial CPD formation (the rate of which should be relatively temperature independent), substantially slows metabolic processes such as DNA repair.…”
Section: Discussionmentioning
confidence: 92%
“…Methods are described in detail in Lamare et al (2006). TDM-2 primary monoclonal antibodies specific to CPDs were supplied by Medical and Biological Laboratories, Nagoya, Japan.…”
Section: Speciesmentioning
confidence: 99%
“…Only the activity of the antioxidant enzyme catalase has been shown not to be thermally sensitive in response to UVR exposure in L. peronii tadpoles [72]. However, the DNA repair mechanisms of enzymatic photoreactivation (EPR) and nucleotide excision repair (NER) have been shown to increase with increasing temperature in ciliates [115], freshwater crustaceans [116], marine macroalgae [117], tobacco cells [118] and echinoid embryos [119], however, Connelly et al [120] found the opposite to be true in Daphnia. The photoprotective mechanism of ROS reduction by enzymatic antioxidant activity has also been found to be thermally sensitive in summer-caught mosquito fish Gambusia holbrooki exposed to UVR [39].…”
Section: Uvr and Abiotic Factors Temperaturementioning
confidence: 99%
“…Kazerouni et al [39] found that the activities of superoxide dismutase and catalase were highest in fish acclimated to the average environmental temperature of 28°C, but was reduced in fish acclimated to lower and higher temperatures (18°C and 32°C). Importantly, the improved efficiency of EPR, NER and antioxidant activity due to changes in temperature has been found to reduce the negative effects associated with UVR exposure on development, survival, metabolic rate and locomotor performance [39,119,120]. Given that EPR, NER and antioxidant activity are thermally sensitive in other organisms, it seems likely that these physiological UVR defences are also thermally sensitive in amphibians.…”
Section: Uvr and Abiotic Factors Temperaturementioning
confidence: 99%
“…For instance, the photorepair in coral planulae is very efficient, as it repairs 50% of UVB-induced DNA damage in 23 min (Reef et al, 2009). Additionally, the photorepair of some species of echinoid embryos removes 50% of CPDs in 0.6 h (Lamare et al, 2006). In fishes, this DNA repair pathway also operates more quickly than nucleotide excision repair (NER), removing damage on a scale of minutes compared with hours or days for NER (Kienzler et al, 2013a).…”
Section: Introductionmentioning
confidence: 99%